The Urgency of Knowledge, Communication and Perception of Islamic Education Management Information Systems - Hasanuddin, Hasanuddin; Hapzi Ali; Kasful Anwar (International Journal of Advanced Multidisciplinary, 2023)
This paper aims to provide an understanding of the urgency of knowledge, communication and perceptions of Islamic education management information systems. The method used in this paper is (Library Research). The research results show that in facing globalization, the world of Islamic education in Indonesia must immediately improve itself to improve the education management information system to support the competitiveness of human resources produced by educational institutions. The information system that will be created must be balanced between the available technological infrastructure and the capabilities of its human resources so that there is no great discrepancy, therefore knowledge, communication and perceptions of Islamic education management information systems are very important to face the challenges of the globalization era.